S17. ZNF804A GENE AND CANNABIS USE: INTERACTION ON THE RISK FOR PSYCHOSIS IN A NON-CLINICAL SAMPLE. (1st April 2018) - Garcia, Jordi Soler; Arias, Barbara; Moya, Jorge; Ibañez, Manuel Ignacio; Ortet, Generós; Fañanás, Lourdes; Fatjó-Vilas, Mar
Abstract: Background: The ZNF804A gene and cannabis use are risk factors for psychosis, both of which have also been associated with schizotypic traits. This study aimed to test whether ZNF804A (rs1344706) modulates the relation between cannabis use and schizotypy levels in a general population sample. Methods: The sample consisted of 389 Spanish non-clinical subjects (43% males, mean age=21.1(2.19)). Schizotypy was evaluated with the three factors of the Schizotypal Personality Questionnaire-Brief (SPQ-B): Cognitive-Perceptual (CP), Interpersonal (I) and Disorganized (D). Subjects were classified as cannabis users or non-users. Multiple linear regressions were conducted to test the effect of genetic and environment factors and their interaction on SPQ-B scores. Sex and anxiety scores (evaluated with SCL) were included as covariates. Results: The analyses showed a significant linear relationship between the ZNF804A and SPQ-I: homozygotes AA showed higher scores (p=0.001). An interaction between cannabis use and rs1344706 on SPQ-CP was observed: among individuals AA, cannabis users presented higher scores than non-users, while among individuals CC, cannabis users presented lower scores compared to non-users (p=0.005). Discussion: These results add evidence on that the ZNF804A modulates schizotypy and suggest that schizotypy levels are influenced by an interaction between the exposure to cannabis and the ZNF804A genotype.